Ventricular fibrillation due to coronary vasospasm. (3rd February 2014) - Naqvi, Syed Yaseen; Hanley, Alan; Crowley, James
Abstract : A 43-year-old woman developed a sudden-onset severe chest pain and breathlessness at home. She collapsed within minutes and received bystander cardiopulmonary resuscitation from her husband. On arrival, the paramedics identified ventricular fibrillation requiring defibrillation. She was admitted to the intensive care unit for observation. A coronary angiogram performed at our hospital demonstrated non-obstructive disease of the right coronary artery. Her antidepressant medications were discontinued and she was discharged. No specific cause was found for the arrhythmia and collapse. One week later, she developed similar chest pain. An ECG showed transient ST-elevation in the inferior leads. Symptoms and ECG changes resolved with sublingual nitroglycerin. During the course of a repeat coronary angiogram the patient developed severe spasm of the right coronary artery associated with typical chest pain and ST-elevation in the inferior leads. She was treated with insertion of a drug-eluting stent and a cardiac defibrillator.